Motivation, Attitude, Years of Service, and Performance of Employees In Health Training Center of Bengkulu Province - Rina Aprianti; S. Effendi; Juliarti Juliarti (Jurnal Sains Kesehatan, 2018)
Performance is the result of the work achieved by an employee in carrying out tasks  that are charged to him in accordance with the responsibilities given to him, which are based on skills, experience and excellence and time with the resulting output reflected well. The purpose of  this study was to study the factors related to employee performance at the Bengkulu Province Health Training Center (Bapelkes). This type of research was Analytical Survey, with Cross Sectional research design. The population in this study were all employees at the Bengkulu Province Health Training Center (Bapelkes) totaling 34 people who were taken using the Total Sampling technique. Data collection in the study used primary and secondary data. Data analysis techniques were carried out by univariate and bivariate analysis. Bivariate analysis using Chi-Square statistical test. The results of this study were: of 34 employees, there were 30 employees (88.2%) had good motivation, 32 employees (94.1%) had favorable attitudes, 24 employees (70.6%) had a service life of ≥5 years, and 31 employees (91.2%) had good performance. There was a significant relationship between motivation and attitude with employee performance. There was no significant relationship between working period and employee performance. Keywords: attitude, employee, motivation, performance, years of service